Shallow- and Deep-Water Ophiura Species Produce a Panel of Chlorin Compounds with Potent Photodynamic Anticancer Activities - Antonina Klimenko; Robin Huber; Laurence Marcourt; Dmitry Tabakaev; Alexey Koval; Salim Sh. Dautov; Tatyana N. Dautova; Jean-Luc Wolfender; Rob Thew; Yuri Khotimchenko; Emerson Ferreira Queiroz; Vladimir L. Katanaev (MDPI AG, 2023)
A Pacific brittle star Ophiura sarsii has previously been shown to produce a chlorin (3S,4S)-14-Ethyl-9-(hydroxymethyl)-4,8,13,18-tetramethyl-20-oxo-3-phorbinepropanoic acid (ETPA) (1) with potent phototoxic activities, making it applicable to photodynamic therapy. Using extensive LC-MS metabolite profiling, molecular network analysis, and targeted isolation with de novo NMR structure elucidation, we herein identify five additional chlorin compounds from O. sarsii and its deep-sea relative O. ooplax: 10S-Hydroxypheophorbide a (2), Pheophorbide a (3), Pyropheophorbide a (4), (3S,4S,21R)-14-Ethyl-9-(hydroxymethyl)-21-(methoxycarbonyl)-4,8,13,18-tetramethyl-20-oxo-3-phorbinepropanoic acid (5), and (3S,4S,21R)-14-Ethyl-21-hydroxy-9-(hydroxymethyl)-4,8,13,18-tetramethyl-20-oxo-3-phorbinepropanoic acid (6). Chlorins 5 and 6 have not been previously reported in natural sources. Interestingly, low amounts of chlorins 1-4 and 6 could also be identified in a distant species, the basket star Gorgonocephalus cf. eucnemis, demonstrating that chlorins are produced by a wide spectrum of marine invertebrates of the class Ophiuroidea. Following the purification of these major Ophiura chlorin metabolites, we discovered the significant singlet oxygen quantum yield upon their photoinduction and the resulting phototoxicity against triple-negative breast cancer BT-20 cells. These studies identify an arsenal of brittle star chlorins as natural photosensitizers with potential photodynamic therapy applications.